2020
DOI: 10.1128/jcm.00075-20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Hepatitis B Virus RNA Levels and Quasispecies Evolution Patterns between Entecavir and Pegylated-Interferon Mono-treatment in Chronic Hepatitis B Patients

Abstract: Hepatitis B virus RNA (HBV RNA) may independently predict virological and serological response. This study aimed to compare dynamic changes in serum HBV RNA levels and its quasispecies evolution patterns between entecavir and pegylated-interferon mono-treatment in chronic hepatitis B patients and to determine its clinical significance during treatment. A TaqMan real-time PCR was used for quantitative analysis. HBV RNA levels were retrospectively determined in serial serum samples from 178 chronic hepatitis B p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Similarly to our results, no significant difference was found between HBV RNA and HBV DNA quasispecies complexity at baseline quasispecies. While the results were similar, we analyzed a different region of the HBV genome (the region of the HBX between nt 1255 to 1611) than the study by Yu et al [ 6 ] (a sequence stretch within the region encoding for the terminal protein domain of the viral polymerase), and our group of patients is more heterogeneous, especially in terms of viral genotype composition. Thus, results from the 2 studies are not directly comparable, and further studies in larger groups of patients are required to confirm the tendency of HBV DNA quasispecies toward higher quasispecies complexity, as shown by mean RHL values.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Similarly to our results, no significant difference was found between HBV RNA and HBV DNA quasispecies complexity at baseline quasispecies. While the results were similar, we analyzed a different region of the HBV genome (the region of the HBX between nt 1255 to 1611) than the study by Yu et al [ 6 ] (a sequence stretch within the region encoding for the terminal protein domain of the viral polymerase), and our group of patients is more heterogeneous, especially in terms of viral genotype composition. Thus, results from the 2 studies are not directly comparable, and further studies in larger groups of patients are required to confirm the tendency of HBV DNA quasispecies toward higher quasispecies complexity, as shown by mean RHL values.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the slower decline of serum HBV RNA levels may also make it possible to study circulating viral quasispecies, even when serum HBV-DNA levels are too low to do so. However, few studies to date have analyzed circulating HBV-RNA quasispecies[ 4 , 6 ] and little data is therefore available on their similarities and differences. Indeed, it is reasonable to think that both quasispecies may display significant differences between them, as they are subjected to different sources of genetic variability, due to the error-prone viral polymerase, contributing to an estimated error rate of approximately 1 per 10 4 -10 5 bp for minus-strand DNA synthesis and approximately 1 per 3.6-15 × 10 4 bp for second-strand DNA synthesis[ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After 5 years of NA treatment, HBV RNA was detected in 14% of the HBV DNA negative patients ( 9 ). Among 122 CHB patients treated with ETV, HBV DNA could not be detected in 90% of patients at week 48, and only 18% of the patients had HBV RNA below the detection limit ( 17 ). Our data showed that compared to the baseline, HBV DNA and HBV RNA both showed a downward trend at week 24, week 48, week 96, year 5, and year 10 after ETV treatment.…”
Section: Discussionmentioning
confidence: 99%